A systematic literature review of studies estimating the risk factor attributable burden in Europe. (20th October 2021) - Gorasso, V; Nazaré Nogaro, J; Charalampous, P; Haagsma, J; Monteiro Pires, S; Von der Lippe, E; Devleesschauwer, B; Plass, D
Abstract: Along with the computation of disability-adjusted life years (DALY), the Global Burden of Disease (GBD) study uses the comparative risk assessment method to estimate the burden attributable to risk factors (RF). The methodology used for GBD studies has undergone continuous improvements through the years and across many independent studies. The European burden of disease network launched a series of systematic literature reviews (SLR) to explore key assumptions used in the European burden of disease (BoD) assessments. The SLR will give an overview of existing studies, including those estimating the BoD attributable to RF and focus on the different computational approaches. The SLR will also help to identify ways to harmonize computational procedures to enhance the comparability of RF attributable burden. The SLR involved four parallel reviews: non-communicable diseases, communicable diseases, injuries and RF. For the latter, we used a search strategy with terms describing the population (GBD area "European region") and terms specifically used in comparative risk assessments (comparative risk assessment [CRA], attributable mortality/burden/risk). Studies published between January 1990 and April 2020 were included, without language restrictions. The search strategy was run in PubMed, Web of Science, Cochrane, and Embase. OpenGrey, OAIster, CABDirect, WHO, and targeted public health agency websites were screened for indexed grey literature. In addition, burden-eu members were asked to supplement the list of publications with any material available in their national public health institutes. The title, abstract, and full-text screening resulted in the final inclusion of 114 publications. The list of publications includes peer-reviewed articles and reports showing a variability in CRA analysis (e.g. use of exposure-response function, relative risks) and other methodological choices. Further data extraction and analysis is in process and will be presented during the workshop.